How and When Does International Migration Policy Travel Across Scales? Understanding the Limits to Migration as Adaptation Through the Lens of Thailand - Ober, Kayly; Sakdapolrak, Patrick (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
Climate change and migration are increasingly becoming a part of policy discussions. One concept, migration as adaptation, has become popularized as a tangible way forward. While some studies focus on how this framing came to be at the international level, few have actually traced how it has traveled across administrative scales to the national and sub-national level. This paper looks to fill this gap and explores migration as adaptation policy in Thailand, a climate-vulnerable country with a highly mobile population. It finds that there is limited discussion of the issue for ideational and institutional reasons, including because migration is seen as negative or a “last resort” by Thai policymakers, limited leverage by relevant policy actors such as IOM within climate change adaptation policymaking arenas, and short-term and short-sighted policy reactions based on disruptive events. Given this, this paper questions the ability of migration as adaptation to travel to lower governance scales in particularly constrained contexts.